A survey on the practices and capabilities in the management of respiratory failure in South East England. (May 2021) - Jha, Abhishek; Vasques, Francesco; Sanderson, Barnaby; Daly, Kathleen; Glover, Guy; Ioannou, Nicholas; Wyncoll, Duncan; Sherren, Peter; Langrish, Chris; Meadows, Chris; Retter, Andrew; Paul, Richard; et al.
Introduction: The variability of acute respiratory distress syndrome management may affect the referral practice to severe respiratory failure centres. We described the management of acute respiratory distress syndrome in our catchment area. Methods: An electronic survey was administered to 42 intensive care units in South-East England. Results: Response rate was 71.4%. High-flow nasal oxygen and non-invasive ventilation were used 'often' in moderate-acute respiratory distress syndrome by 46.7% and 60%. During invasive ventilation, 90% preferred pressure control, targeting tidal volumes of 6–8 ml/kg (53.3%) or 4–6 ml/kg (46.7%). Positive end-expiratory pressure was selected by positive end-expiratory pressure/inspiratory fraction of oxygen tables (50%) or decremental positive end-expiratory pressure trials (20%). Neuro-muscular blockers were widely used, although routinely by only 3.3%. High-frequency oscillatory ventilation (10%) and inhaled nitric oxide (13.3%) were rarely used. None used oesophageal manometry. Recruitment manoeuvres were used 'often' by 26.7%. Equipment (90%) and protocols (80%) for prone position were common, with sessions mostly lasting 12–18 h. Conclusions: Although variable, practice well reflected the available evidence. Proning was widely practiced with good availability of educational resources and protocolised care.